Age-related features of alpha rhythm dynamics: a brief review - I.S. Polikanova; I.N. Mikheev; S.V. Leonov; O.V. Martynova (Клиническая и специальная психология)
In this mini-review, the age-related features of alpha rhythm dynamics, its generation sources, and its connection to cognitive functions are discussed. The review focuses on a brief systematization of data regarding the alpha rhythm of human brain bioelectrical activity and its informativeness in determining the biological age of the human brain. The alpha rhythm is characterized by high individual stability and exhibits pronounced age-related dynamics in its U-shape. The peak frequency of the alpha rhythm increases from infancy to young adulthood and then decreases during brain aging. Discussions about the sources of alpha rhythm generation are still ongoing. Current data show a lack of a clear connection between the peak frequency of alpha rhythm and human cognitive abilities and intelligence. Parameters of the alpha rhythm, such as individual stability, genetic predisposition, and age-related characteristics, make it a promising marker for both normative development and brain aging in determining cognitive and biological age.